Pemanfaatan Teknologi Informasi dan Komunikasi untuk Meningkatkan Akses Pasar Produk Perikanan - Mira Sukma; Firman Firman; Gea Ananda Putri Septiyanti; Nanditha Dwi Zirani; Sherlina Sonia Putri (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
The utilization of information and communication technology (ICT) has become a strategic instrument in expanding market access for fishery products, especially for small-scale enterprises in coastal areas. This study aims to examine the forms of ICT utilization in fisheries marketing, identify the barriers faced by business actors, and analyze its impact on market access expansion. The research employed a qualitative descriptive method by reviewing 15 national and international scientific journals. The findings show that the use of digital marketplaces such as Aruna and Shopee, as well as social media platforms like Instagram and WhatsApp, has positively contributed to increased sales volume, wider geographic market reach, and reduced promotional costs. However, the adoption of ICT still encounters barriers such as low digital literacy, limited internet infrastructure, and lack of trust in digital systems. This study emphasizes the necessity of institutional support and digital literacy training to accelerate inclusive digital transformation in the fisheries sector. The study contributes to the development of relevant and sustainable technology-based marketing strategies for fishery MSMEs in Indonesia.